The underused hip in ipsilaterally orthotics-dependent children. (August 2015) - Sallam, Asser; Ziegler, Christian M.; Jansson, Volkmar; Heimkes, Bernhard
Background: The aim of this investigation is the development of primarily healthy hips in children who have required orthoses/protheses over the long term due to ipsilateral distally located deformities of the leg. These children show ipsilateral in-toeing gait and Duchenne's limping followed by a coxa valga antetorta and facultative hip decentration. A practical question is whether these hips are in danger of decompensation. An additional theoretical question is how the external shape and internal architecture changes if a primarily healthy hip is underused. Methods: Ten children with healthy hips who are unilaterally long-term orthotics/prosthetics-dependent agreed to undergo an instrumental gait analysis. The results were analyzed and correlated with clinical findings, a common activity score and planimetric radiographic data. Results: The intra-individual comparison revealed a number of significant changes in the hip of the deformed leg ( p < 0.05). Clinically, the internal rotation was increased (15° ± 4.2°), while the external rotation was diminished (13° ± 1.3°). Radiologically, the projected caput–collum–diaphyseal angle, the lesser trochanter to articular surface distance and the head–shaft angle were increased by 11.1° ± 15.4°, 5.8 ± 4.2 mm and 11.9° ± 0.6°, respectively. Both the Sharp and acetabular angles were increased, the former by 3.6° ± 0.6° and the latter by 3.2° ± 0.6°. Kinetic gait analysis showed increased stride length (6.8 ± 3.7 cm), shortened stance phase (6.6 ± 1.6 %) and reduced forces transmitted to the ground (92.2 ± 34.3 N). The kinematic analysis showed increased hip abduction (14.0° ± 8.2°), while the pelvic obliquity was not significantly changed (0.01° ± 0.01°). Conclusions: Duchenne's limp and lack of weight-bearing stress are the decisive pathogenic factors of the underused coxa valga and acetabular dysplasia. These changes follow the mechanobiological concept of "function modifies design", which means function influences external shape and internal architecture of bones and joints. As a practical consequence we recommend that one pelvic radiograph be performed as a precaution at the end of puberty of children with these conditions. Level of evidence: Level II retrospective study.